Ontology and semantic web approaches for heterogeneous database access - Yusof, Mohd Kamir; Abdul Rahman, Mohd Nordin; Mat Amin, Mat Atar (2011)
This paper presents about implementation of ontology and semantic approaches for accessing data from heterogeneous database. The purpose of this implementation is to retrieve relevant data and give relevant information to web users. The process of ontology and semantic are related. Two major processes in ontology are semantic mapping and extracting wrapper ontology. The main process for semantic web is to manipulate data into meaningful information. In this research, simple application was develop by using JAVA technology. JAVA technology was chosen because this technology have Jena library. This library is provide API and support SPARQL. After that, several experiments were done, and the results indicate implementation of ontology and semantic web approaches able to show relevant information to web users.